Institutions and Foreign Subsidiary Growth in Transition Economies: The Role of Intangible Assets and Capabilities - Kafouros, Mario; Aliyev, Murod (Journal of management studies, 2016)
Although transition economies experience significant institutional transformations that vary in their degree and pace, scholarly knowledge of what distinguishes more successful foreign subsidiaries from less successful ones in such environments is limited and inconsistent. We enhance the understanding of this subject by examining how variations in the institutional development of transition economies influence the usefulness of a subsidiary's intangible assets and capabilities and, in turn, their effectiveness in enhancing its growth. Prior research assumes that foreign subsidiaries that operate in any given environment are always better off when they possess strong intangible assets and capabilities. Our analysis of more than 33,000 observations in 14 transition economies challenges this view and enables us to explain why some subsidiaries grow more quickly in less‐developed institutional environments, whereas others more quickly in countries with institutions that are more developed. More specifically, we show that although a subsidiary's intangible assets enhance its growth in transition economies with stronger institutions, these effects are particularly weak or insignificant in transition countries with less developed institutional environments. Conversely, a completely different pattern emerges for subsidiary capabilities, with their marginal effects on subsidiary growth being significantly higher in countries that are institutionally less developed than in transition countries with more developed institutions.